Exploring Custodianship Roles and Responsibilities for Cadastral Data in the Context of the South African Spatial Data Infrastructure - Coetzee, Serena Martha (University of Pretoria, 2021)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2021.